Cannabis sativa-derived carbon dots co-doped with N–S: highly efficient nanosensors for temperature and vitamin B12. (24th October 2019) - Tiwari, Pranav; Kaur, Navpreet; Sharma, Vinay; Kang, Hyeonggon; Uddin, Jamal; Mobin, Shaikh M.
Abstract : Cannabis sativa -derived carbon dots as efficient nanosensors for temperature and vitamin B12 . Abstract : With the enhancement in biomimetic and bioinspired synthesis approaches, plant-derived nanostructures provide the most suitable synthesis alternatives in terms of being non-toxic, economical and eco-friendly. The present work focused on Cannabis sativa -derived carbon dots co-doped with nitrogen and sulphur (N–S@CsCD ) as a nanosensor. N–S@CsCD exhibited size distribution in the range of 4–6 nm and showed an excitation-independent emission behaviour with an emission wavelength around 414 nm. The XPS spectra confirmed the presence of heteroatom doping by nitrogen and sulphur with the concentrations of 10.71% and 1.94%, respectively. N–S@CsCD showed excellent stability to pH, time and salt concentration. Interestingly, N–S@CsCD exhibited a reversible temperature-responsive fluorescence "turn-off" behaviour. Furthermore, N–S@CsCD showed a selective fluorescence "turn-off" behaviour in the presence of vitamin B12 (VB12 ), with a limit of detection of 7.87 μg mL −1 . The fluorescence lifetimes of N–S@CsCD with and without VB12 were similar, which implied that the sensing behaviour was purely static in nature. Moreover, N–S@CsCD showed biocompatible and non-toxic behaviours with very high cell viability. The fluorescence nature of N–S@CsCD was further evaluated for intracellular imaging.